2018
DOI: 10.2514/1.g003382
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and Balancing for High-Performance Computation of Optimal Controls

Abstract: It is well-known that proper scaling can increase the efficiency of computational problems. In this paper we define and show that a balancing technique can substantially improve the computational efficiency of optimal control algorithms. We also show that non-canonical scaling and balancing procedures may be used quite effectively to reduce the computational difficulty of some hard problems. These results have been used successfully for several flight and field operations at NASA and DoD. A surprising aspect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…It is also worth noting that DIDO does not require a "guess" to use the software. 30 In order words, the solution presented in Figures 1 through 4 is "unbiased" from a user's perspective. Because there was no clear difficulty in generating this…”
Section: A Pseudospectral Answer To the Challenge Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth noting that DIDO does not require a "guess" to use the software. 30 In order words, the solution presented in Figures 1 through 4 is "unbiased" from a user's perspective. Because there was no clear difficulty in generating this…”
Section: A Pseudospectral Answer To the Challenge Problemmentioning
confidence: 99%
“…At NASA and elsewhere in the industry, it is not sufficient to generate a solution as presented in Figures 1 through 4 without subjecting it to a battery of mathematical and engineering tests. Furthermore, an argument that the residuals are small (e.g., 10 −8 ) is well-established to be irrelevant 15,17,30,31 because it is possible to produce a wrong answer -even an infeasible one -with very small "collocation errors." A standard industry practice in testing the accuracy of a control solution is to subject it to an established propagation technique and compute certain critical functions of the propagated state variables; see Refs.…”
Section: An Independent Verification Of Feasibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, Algorithm 1 solves a dimensionless P1 for better numerical performance. Previous research has revealed scaling and balancing at the optimal control level contribute to increasing the efficiency of a solution algorithm 41 . Nondimensionalization is the scaling technique used in this article; details about this technique can be found in the reference 29 …”
Section: Hp‐pseudospectral Sequential Convex Programmingmentioning
confidence: 99%
“…Many of the advancements in the spectral algorithm are implemented in DIDO © [30,39], a stateof-the-art MATLAB optimal control toolbox for solving optimal control problems. As noted earlier, the condition number of the linear matrix equations involved in the spectral algorithm grows as N 2 k , k = 0, 1, .…”
Section: Solvementioning
confidence: 99%